2008
DOI: 10.1371/journal.pone.0003680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Intestinal Parasitic Infection among Children in an Urban Slum of Karachi

Abstract: BackgroundIntestinal parasitic infections are endemic worldwide and have been described as constituting the greatest single worldwide cause of illness and disease. Poverty, illiteracy, poor hygiene, lack of access to potable water and hot and humid tropical climate are the factors associated with intestinal parasitic infections. The study aimed to estimate prevalence and identify factors associated with intestinal parasitic infections among 1 to 5 years old children residing in an urban slum of Karachi Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
184
9
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(236 citation statements)
references
References 21 publications
31
184
9
12
Order By: Relevance
“…Our finding was in agreement with the previous epidemiological studies conducted in Malaysia 5-9 and abroad. 4,22,23 This could be because as the child grows older, the exposure to the sources of infection increases. As for preschool and school-going children, they are more independent, active, and inquisitive and are interested in learning new things in their surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding was in agreement with the previous epidemiological studies conducted in Malaysia 5-9 and abroad. 4,22,23 This could be because as the child grows older, the exposure to the sources of infection increases. As for preschool and school-going children, they are more independent, active, and inquisitive and are interested in learning new things in their surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…Lower SES and poverty were also significant risk factors for STH infections. 22,25,26 Non-working parents and family with low household income were taken as a proxy measure of poverty, which was also significantly associated with STH infections. This study reported low household income was a significant predictor for STH infections among Temuan, Semelai and Mah Meri subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Intestinal parasitic infections deprive the poorest of health, contributing to economic instability and social marginalization. 3 Death and other serious complications can occur if cases of intestinal parasitosis are left untreated especially in children. 1 In Nigeria, intestinal parasitic infection constitutes a major public health challenge.…”
Section: Introductionmentioning
confidence: 99%
“…4 Poorly planned housing, improper waste disposal, gross environmental pollution and poor environmental situations among others are driving forces for this observation. 5 Illiteracy, absence of clean drinking water, and poverty has been shown to promote infection with intestinal parasites 3 and these factors are rife in most rural communities in Nigeria. 6,7 Although data on prevalence of human intestinal parasitic infection in Nigeria is common, there is no published data from Okada community, Edo State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%